2014
DOI: 10.1111/j.2047-6310.2014.226.x
|View full text |Cite
|
Sign up to set email alerts
|

Motivational interviewing targeting diet and physical activity improves adherence to paediatric obesity treatment: results from the MIValues randomized controlled trial

Abstract: Background Adherence is a challenge in obesity treatment. Motivational interviewing (MI) may promote patient adherence. MI Values is a randomized controlled trial of MI implemented as an adjunct to an adolescent obesity treatment (T.E.E.N.S.). Objective Assess effects of MI Values on T.E.E.N.S. attrition and adherence. Methods Participants were randomized to MI (n=58) or control (n=41). At weeks 1 and 10, MI participants had brief MI sessions; controls viewed health education videos. All participants conti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
66
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 25 publications
5
66
0
1
Order By: Relevance
“…Nine studies had measured body mass index (BMI) scores. Of these, eight found greater reductions in BMI in the intervention group than controls . One study found no impact on BMI …”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Nine studies had measured body mass index (BMI) scores. Of these, eight found greater reductions in BMI in the intervention group than controls . One study found no impact on BMI …”
Section: Resultsmentioning
confidence: 95%
“…Management or frequency of symptoms was examined in 44 studies. Four of the studies that had investigated symptom frequency found no differences, and 25 studies reported reduction of symptoms and/or awareness of symptom triggers . Ten studies from interventions tailored to children and adolescents with asthma reported improved asthma control and decreased number of asthma exacerbations.…”
Section: Resultsmentioning
confidence: 97%
“…Strength-based approaches [24], [25••] invoke PYD concepts and operationalize them into clinical contexts, engaging young people around health behavior decisions by ensuring that each teen’s assets and resources are elucidated and incorporated into clinical problem solving and decision-making. Among strength-based approaches, Motivational Interviewing [26••], [27] continues to garner significant attention as a foundation for effective person-centered clinical counseling to optimize health behaviors [28], [29], [30]. …”
Section: Treatmentmentioning
confidence: 99%
“…In adolescents, health coaching is a promising strategy that promotes healthy behaviors using validated techniques like motivational interviewing [14,15]. Although data from randomized clinical trials in adolescents are limited [1618], a health coaching behavior modification program may be an effective, low-cost, personalized and flexible program that can be implemented through clinical or community settings.…”
Section: Introductionmentioning
confidence: 99%